Is selective nodal irradiation in non-small cell lung cancer still safe when using IMRT? Results of a prospective cohort study. Issue 2 (November 2016) - Martinussen, Hanneke M.A.; Reymen, Bart; Wanders, Rinus; Troost, Esther G.C.; Dingemans, Anne-Marie C.; Öllers, Michel; Houben, Ruud; De Ruysscher, Dirk; Lambin, Philippe; van Baardwijk, Angela
Abstract: Background and purpose: Isolated nodal failures (INF) are rare after 3D-conformal radiotherapy (3D-CRT) for stage III non-small cell lung cancer (NSCLC). Since incidental nodal irradiation doses are lower with Intensity Modulated Radiation Therapy (IMRT) than with 3D-CRT, INF may be higher after IMRT. We therefore investigated the incidence of INF after IMRT in stage III NSCLC patients. Materials and methods: Stage III NSCLC patients undergoing radical radiotherapy using IMRT in the period January 2010 till March 2012 were included. The primary endpoint was the rate of INF, secondary endpoints included patterns of failure, progression free survival (PFS), overall survival (OS) and toxicity. Results: 183 stage III NSCLC patients were enrolled. With a median follow-up of 58.0 months 2.2% of patients had an INF. The median PFS was 15.0 months, the median OS 19.5 months. Patterns of recurrence: 2.2% INF, 11.5% local and 2.7% loco-regional recurrence, 26.8% distant metastases only, 18.0% a combination of local/loco-regional and distant metastases, and 38.3% patients without recurrence. One INF was out of field, in adjacent lymph nodes. Acute toxicity was limited. Discussion: Selective nodal irradiation using IMRT in stage III NSCLC patients results in a low in-field incidence of INF (2.2%), similar to 3D-CRT, and may thus be considered safe.